Risk Factors for Occupational Diseases Due to Exposure to Ultraviolet Rays among Agricultural and Outdoor Workers - Kholid Rosyidi Muhammad Nur; Novia Narulia Sari; Hanna Salsabila; Andika Firda Azza Zahra; Monica Zhafirah Nur Nashirah; Enggal Hadi Kurniyawan; Dicky Endrian Kurniawan (Health and Technology Journal (HTechJ), 2024)
As a country with a tropical climate with high humidity, relatively high air temperature, and hot solar radiation, it can disrupt the psychological and social conditions of field workers such as farmers. Farmers have a higher risk due to their work activities under the hot sun, which has a dangerous UV index. In addition, the lack of understanding of the factors and how to prevent farmers from being exposed to UV light has caused many cases of farmers getting diseases such as heatstroke, cataracts, and skin cancer due to exposure to UV rays. This study aims to know the risk factors for the dangers of UV light and the use of PPE for agricultural workers and workers in outdoor environments. This study used the literature review method. The search was based on three databases, Science Direct, PubMed, and Google Scholar, with the last five years of publication (2019-2023). Workers who do a lot of outdoor activities, such as farmers, have a higher risk of developing skin cancer due to the scorching sun with a harmful UV index. One of the risk factors for skin cancer in agricultural workers is exposure to ultraviolet radiation (UVR) and heat. Exposure to ultraviolet radiation (UVR) is also a risk factor for skin cancer, heatstroke, and cataracts in agricultural and outdoor workers. In addition, hazardous equipment can also be another risk factor for cancer in farm workers. Agricultural workers and workers outside the field must know how to maintain their health by using shade seeking, using PPE, and using sunscreen from the dangers of UV rays so that they do not experience skin cancer, heatstroke, and cataracts.